Impact of technical and professional developments on audit risks Review study - Waheed Mahmood Ramo; Abdulwahid Ghazi Mohammed (Journal of Techniques)
The research provides an attempt to identify the effects of technical and professional developments on audit risks, important of these developments are cloud computing, blockchain, electronic commerce, fair value and corporate governance. Considering that these developments represent the modern environment for auditing in general and auditing risks in particular. Therefore, the nature of these developments and their relationship to auditing and their impact on audit risks have been clarified, leading to the determination of the implications of these developments on audit risks and the requirements to keep up with developments (technical and professional) in the field of audit risk assessment.